Maqashid Syariah dalam Pengasuhan Anak di Indonesia Telaah Hadis Nabi dan Implikasinya dalam Hukum Keluarga Islam - Abror, Mhd.; Akbarizan, Akbarizan; Munir, Akmal Abdul (Jurnal El-Thawalib, 2025)
Maqashid Sharia plays a crucial role in shaping parenting patterns that align with Islamic values. The hadiths of Prophet Muhammad (peace be upon him), as a primary source of Islamic teachings, provide normative guidance for parents in protecting and educating their children and families. The urgency of this research lies in the pressing need to integrate the principles of Maqashid Sharia into parenting practices amid the challenges of modernity and social change, while simultaneously strengthening the foundation of Islamic family law in Indonesia to remain relevant to Sharia values. This study aims to examine the hadiths of Prophet Muhammad (peace be upon him), particularly those related to child education and parenting from the perspective of Maqashid Sharia, and to analyze their implications for Islamic law in Indonesia. The research adopts a qualitative approach using thematic analysis of relevant hadiths. The primary sources include Law No. 1 of 1974 and its amendment, Law No. 16 of 2019, as well as the Compilation of Islamic Law (KHI) and the Hadiths of Prophet Muhammad (peace be upon him). Data were collected through documentation and literature study techniques. The findings indicate that parenting practices based on Maqashid Sharia contribute positively to fostering an Islamic, happy, and harmonious family environment. Furthermore, the study highlights the importance of integrating Maqashid Sharia principles into family law policies and emphasizes the need to enhance parental education to ensure the implementation of parenting practices in accordance with Islamic teachings.